SUPPORTING URBAN LIVING FOR PART-TIME ENTREPRENEURIAL VENTURES - Ismail, Norina Haziqah; Mohamed, Suhana; Abdullah, Nur Najmina Yasmin; Mohd Noor, Jannah Munirah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study aims to investigate the challenges and support systems for part-time urban entrepreneurial activities in Johor Bahru, Malaysia. It examines how urban space conditions the possibility of sustainability and growth of such initiatives, particularly in the case of marginalized groups, such as the urban poor. Entrepreneurial resilience, access to digital infrastructure, and the socio-economic context determine whether part-time entrepreneurship is a viable option. The study is statistical and measures information in a way that evaluates the lives, barriers, and resource needs of part-time entrepreneurs. The implications aim to inform targeted policy interventions and urban development approaches that foster inclusive entrepreneurial ecosystems and support the creation of sustainable livelihoods in rapidly growing urban areas.